STRENGTHENING THE RADEC MODEL IN SCIENCE LEARNING TO SUPPORT STUDENTS' HIGHER-ORDER THINKING SKILLS: SYSTEMATIC LITERATURE REVIEW - Siti Lami'ah; Intan Sari Rufiana; Mardhatillah; Aynin Mashfufah; Slamet Arifin (Jurnal Cakrawala Pendas, 2026)
Science learning at the elementary school level requires a pedagogical approach that can encourage the development of higher-order thinking skills (HOTS) as part of improving the quality of the learning process. The RADEC (Read, Answer, Discuss, Explain, Create) model is considered relevant because it includes systematic, collaborative learning stages, and is oriented towards knowledge construction. Based on this need, this study aims to examine the forms of strengthening the RADEC model in science learning and its contribution to the development of students' HOTS. This study used the Systematic Literature Review (SLR) method by analyzing scientific articles that met the criteria for eligibility and relevance. The results of the review indicate that strengthening RADEC is carried out through the integration of contextual media, the development of HOTS-based teaching tools, the implementation of collaborative strategies, and the use of authentic assessments. These various forms of strengthening play a role in optimizing the RADEC stages, thereby supporting the improvement of analytical, evaluative, creative, scientific communication, and active participation skills of students. Overall, the SLR findings indicate that RADEC has substantive potential in strengthening the quality of science learning and supporting the achievement of higher-order thinking skills in elementary school students.